Biohybrid catalysts for sequential one-pot reactions based on an engineered transmembrane protein. Issue 4 (29th January 2019) - Sauer, D. F.; Qu, Y.; Mertens, M. A. S.; Schiffels, J.; Polen, T.; Schwaneberg, U.; Okuda, J.
Abstract : A two-step one pot reaction sequence consisting of artificial metalloprotein olefin metathesis and hydrogenation was performed yielding 1, 2-diphenylethane derivatives. Abstract : A one-pot cascade reaction sequence to obtain 1, 2-diarylethanes from styrenes was developed. The cascade reaction comprises an olefin cross metathesis and a hydrogenation step with two biohybrid catalysts. One biohybrid catalyst is based on the engineered transmembrane proteinFhuA harboring a Grubbs–Hoveyda-type ruthenium carbene complex and the other one harbors a rhodium(i ) complex. Both active sites are covalently anchored via a modified N-heterocyclic carbene (NHC).